IMPACT OF SUBSTITUENTS IN INDOLOBENZAZOCIN-8-ONE DERIVATIVES ON ANTICANCER ACTIVITY: INSIGHTS FROM MOLECULAR DOCKING AND ADMET PREDICTIONS - ARTHORN LOISRUANGSIN; SASIWADEE BOONYA-UDTAYAN; WEENAWAN SOMPHON (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of the study is to explore how substitutions modulate indolobenzazocin-8-one’s anticancer activity and advantages over taxanes using computational modeling. Methods: Molecular docking predicted binding affinities (Ei, kcaL/moL) at β-tubulin’s colchicine site, while ADMET models evaluated physicochemical/ pharmacokinetic properties. Spearman’s rank correlation analysis was employed for assessing structural- activity relationships. Results: Cytotoxicity was primarily driven by cellular permeability, evidenced by a strong negative correlation between lipophilicity and potency (logD7.4-IC₅₀: ρ=−0.90, p=0.037), unlike the weak, non-significant association with binding affinity (Ei-IC₅₀: ρ=0.46, p=0.434). Methoxy substitution weakened binding (ΔEi increased up to 4.2 kcaL/moL) and had non-linear lipophilicity effects (mono-substitution: ΔlogD7.4=+0.031; di-substitution: ΔlogD7.4=−0.128). Hydroxy substitution enhanced affinity (ΔEi=−1.58 kcaL/moL) but compromised permeability (ΔlogD7.4=−0.095). The optimized lead compound balanced these trade-offs, showing high intestinal absorption (Caco-2 permeability (log cm/s)=−5.033) and low P-glycoprotein efflux risk (probability=0.117). Conclusion: Substitutions affect anticancer activity by altering both hydrophobicity and binding affinity. Unsubstituted indolobenzazocin-8-one demonstrated the most potent anticancer activity. In addition, its drug-like properties and bypass of P-gp-mediated resistance position it as a superior oral alternative to taxanes.